Automatic risk assessment integrated with activity segmentation in the order picking process to support health management. Issue 1 (2020) - Hara, Tatsunori; Li, Yangxu; Ota, Jun; Arai, Tamio
Abstract: The order picking (OP) process includes several manual activities in which OP operators frequently load heavy items in awkward postures. Warehouse managers must manage operators' health risks by determining an improvement strategy for the OP environment. This study proposes a technical method for segment picking activities and integrate them with posture risk assessment based on an ergonomic evaluation tool. We developed an analytical system using an inertial measurement unit-based motion capture device to measure and report the risk distribution of every type of picking activity. The experimental results demonstrate that the proposed method quantifies the effect of different environments on each operator's ergonomic risk.